อิทธิพลของความฉลาดทางอารมณ์ ความสามารถในการเผชิญและฟันฝ่าอุปสรรคที่มีต่อคุณลักษณะการเรียนรู้ด้วยการนำตนเองของนักศึกษาการศึกษานอกระบบและการศึกษาตามอัธยาศัยในกรุงเทพมหานคร - สรวิชญ์ สหพิบูลย์ชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purposes of this research were to 1) study the levels of emotional quotient and adversity quotient and self-directed learning characteristics of non-formal and informal education students in Bangkok Metropolitan area and 2) study the influence of emotional quotient and adversity quotient toward self-directed learning characteristics of non-formal and informal education students. The sample group was 379 non-formal and informal upper secondary education students, which selected using multi – stage random sampling. The research instruments were a personal factors questionnaire, an emotional quotient questionnaire, an adversity quotient questionnaire, and a self-directed learning characteristics questionnaire. The data were analyzed using frequencies (n), percentage (%), Mean (x̄ ), Standard Deviation (SD), Pearson’s product moment correlation coefficient, and enter multiple regression. The results of the study were as follow: 1. The overall level of emotional quotient of non-formal and informal education students in Bangkok Metropolitan was reported at the middle level (x̄ =2.93/4). The levels of three aspects of emotion quotient were also reported at the middle levels (x̄ =3.01/4), (x̄ =2.81/4), and (x̄ =2.98/4). The overall level of adversity quotient of non-formal and informal education students was reported at the middle level (x̄ =127.89/200). The levels of four aspects of adversity quotient were also reported at the middle levels (x̄ =31.72/50), (x̄ =32.88/50), (x̄ =31.51/50), and (x̄ =31.78/50). The overall level of self-directed learning characteristics of non-formal and informal education students was reported at the middle level (x̄ =3.60/5). The self-directed learning characteristics in seven aspects, only one in self-acceptance were reported at the high level (x̄ =3.74/5), whereas the other six aspects were reported at the middle levels (x̄ =3.43/5), (x̄ =3.65/5), (x̄ =3.58/5), (x̄ =3.64/5), (x̄ =3.61/5), and (x̄ =3.50/5). 2. The emotional quotient and self-directed learning characteristics of non-formal and informal education students in Bangkok Metropolitan were positive significantly correlated at .05 level (r=0.47). The adversity quotient and self-directed learning characteristics of non-formal and informal education students were positive significantly correlated at .05 level (r=0.28). The emotional quotient and adversity quotient of non-formal and informal education students were positive significantly correlated at .05 level (r=0.21). Variables that could predict the self-directed learning characteristics of non-formal and informal education students at .05 level consisted of emotional quotient and adversity quotient. They jointly predicted the self-directed learning characteristics of non-formal and informal education students at low level (26%). The standardize formula derived from the analysis could be described as follow: Yself-directed learning characteristics = 0.43Xemotional quotient + 0.19Xadversity quotient